Tối ưu hóa phản ứng thủy phân mật bò cho quy trình tách axit cholic bằng phương pháp bề mặt đáp ứng - An, Trần Bội; Vương, Phan Minh; Thanh Tùng, Phạm Cao; Thảo, Phan Thanh (Vietnam Journal of Chemistry, 2017)
Hydrolysis reaction of cow bile was used to convert bile acid into free cholic acid. This study examined the implementation conditions of the hydrolysis reaction to optimize the performance obtained free acid using RMS method combined with CCD model. Meanwhile reaction yield and cholic acid content was determined by HPLC-ELSD method. Research results showed that a good connection could establish between the concentration of free cholic acid converting from the conjugate acid hydrolysis and temperature, concentration of NaOH, hydrolysis time. Response surface model was used to optimize the hydrolysis conditions. Highest free cholic acid content (98.66 to 98.91 %) was obtained in optimal conditions with 10.38 % NaOH concentration, at 92.35 oC, for 7.25 hours. Keywords. Bile acid, hydrolysis, cholic acid.